2013
DOI: 10.1590/s1679-62252013000400013
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphological patterns of the fishes inhabiting the tide pools of the Amazonian Coastal Zone, Brazil

Abstract: The present study was based on the identification of the ecomorphological patterns that characterize the fish species found in tide pools in the Amazonian Coastal Zone (ACZ) in the Pará State, Brazil. Representatives of 19 species were collected during two field campaigns in 2011. The dominance, residence status, and trophic guild of each species were established, and morphometric data were obtained for up to 10 specimens of each species. A total of 23 ecomorphological attributes related to locomotion, positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 49 publications
1
15
0
4
Order By: Relevance
“…The trophic distance matrix was constructed using the trophic guild classification. A value of one was attributed to the pair of species belonging to the same guild and a value of two for species belonging to different guilds, as proposed by Soares et al (2013) (S6 -Available only as online supplementary file accessed with the online version of the article at http://www.scielo.br/ni).…”
Section: Tabmentioning
confidence: 99%
See 2 more Smart Citations
“…The trophic distance matrix was constructed using the trophic guild classification. A value of one was attributed to the pair of species belonging to the same guild and a value of two for species belonging to different guilds, as proposed by Soares et al (2013) (S6 -Available only as online supplementary file accessed with the online version of the article at http://www.scielo.br/ni).…”
Section: Tabmentioning
confidence: 99%
“…Ecomorphological patterns in assemblages could identify species groups that exploit the same ecological resource independently of their phylogenetic relationships (Oliveira et al, 2010;Soares et al, 2013). However, most of the ecomorphological studies in Neotropical fish communities have focused on cis-Andean ecosystems (Casatti, Castro, 2006;Ferreira, 2007;Oliveira et al, 2010;Soares et al, 2013;Neves et al, 2015;Pessanha et al, 2015;RoaFuentes et al, 2015;Novakowski et al, 2016;Prado et al, 2016), which have shown significant relationships between morphological attributes that respond to ecological affinities such as trophic ecology or habitat use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This order exhibits a high functional diversity of head, mouth and nose morphology, which suggests trophic specializations (Albert, Crampton, 2005) if we consider that morphology is related to feeding mode and habitat use (Winemiller et al, 1995;Oliveira et al, 2010;Soares et al, 2013). For example, rhamphichthyids have an elongated snout with a terminal and small oral cavity that facilitates 2 e160144 [2] the capture of insect larvae in cavities in the streambed (Albert, Crampton, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cunha et al 2007, Cunha et al 2008, Godinho & Lotufo 2010 and Southeast Brazil (e.g. Barreiros et al 2004, Macieira & Joyeux 2011, with many studies focusing on community ecology of tide pools (but see Soares et al 2013 for an ecomorphological approach).…”
Section: Introductionmentioning
confidence: 99%